Efficacy and safety of a routine early invasive strategy after fibrinolysis stratified by glycoprotein IIb/IIIa inhibitor use during percutaneous coronary intervention: a pre-specified subgroup analysis of the TRANSFER-AMI randomised controlled trial. Issue 11 (21st January 2014) - Russo, Juan J; Goodman, Shaun G; Cantor, Warren J; Fitchett, David; Heffernan, Michael; Borgundvaag, Bjug; Ducas, John; Cohen, Eric A; Džavík, Vladimír; Mehta, Shamir R; Buller, Christopher E; Yan, Andrew T; et al.
Abstract : Objective: We evaluated the efficacy and safety of an early invasive strategy post-fibrinolysis in relation to glycoprotein (GP) IIb/IIIa inhibitor use. Methods: The Trial of Routine Angioplasty and Stenting after Fibrinolysis to Enhance Reperfusion in Acute Myocardial Infarction (TRANSFER-AMI) randomised 1059 ST elevation myocardial infarction patients to an early invasive strategy or standard therapy post-fibrinolysis. The primary end point was the composite of death, reinfarction, recurrent ischaemia, new or worsening heart failure, or cardiogenic shock at 30 days. In this pre-specified analysis, we examined efficacy and safety outcomes of an early invasive strategy after stratification by GPIIb/IIIa inhibitor use, which was permitted during percutaneous coronary intervention (PCI) at the discretion of the treating physician. Results: A total of 695 patients (65.6%) received GPIIb/IIIa inhibitors. There was significant heterogeneity (p<0.001) in the efficacy of an early invasive strategy compared to standard therapy, between the strata with GPIIb/IIIa inhibitor use (primary end point 9.6% vs 22.3% respectively, p<0.001) and without GPIIb/IIIa inhibitor use (primary end point 14.8% vs 10.4% respectively, p=0.21). Patients who received GPIIb/IIIa inhibitors had lower Global Registry of Acute Coronary Events (GRACE) risk scores compared to those without GPIIb/IIIa inhibitor use (median 121 vs 130, p<0.001). After adjusting for the interaction between GRACE risk score and treatment assignment, the heterogeneity in the efficacy of an early invasive strategy with respect to GPIIb/IIIa inhibitor use was no longer significant (p interaction=0.08). Conclusions: The apparent difference in the efficacy of an early invasive strategy between GPIIb/IIIa inhibitor strata likely reflects an association between GPIIb/IIIa inhibitor use and baseline risk. GPIIb/IIIa inhibitor use during PCI at the discretion of the treating physician does not appear to modulate the efficacy of an early invasive strategy post-fibrinolysis. Clinical Trial Registration: http://www.clinicaltrials.gov/ct2/show/NCT00164190, NCT00164190 .